2011
DOI: 10.1007/s12011-011-9054-5
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Fluoride and Blood Pressure? An Environmental Study

Abstract: The relationship between intakes of fluoride (F) from drinking water and blood pressure has not yet been reported. We examined the relationship of F in ground water resources (GWRs) of Iran with the blood pressure of Iranian population in an ecologic study. The mean F data of the GWRs (as a surrogate for F levels in drinking water) were derived from a previously conducted study. The hypertension prevalence and the mean of systolic and diastolic blood pressures (SBP & DBP) of Iranian population by different pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 12 publications
1
12
0
2
Order By: Relevance
“…The result of this study revealed significant increases in systolic pressure, diastolic pressure, mean arterial pressure (MAP), and decrease nitric oxide (NO) levels in rats exposed to graded doses of NaF (150 ppm, 300 ppm and 600 ppm) compared with the control. This study therefore corroborates the study of Amini et al () who reported on the relationship between fluoride concentrations in ground water and the incidence of high blood pressure in the exposed population. Nitric oxide produced from the vascular endothelium helps to maintain a continuous vasodilator tone that is essential for the regulation of blood flow, blood pressure, platelet aggregation and vasodilation (Hermann et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The result of this study revealed significant increases in systolic pressure, diastolic pressure, mean arterial pressure (MAP), and decrease nitric oxide (NO) levels in rats exposed to graded doses of NaF (150 ppm, 300 ppm and 600 ppm) compared with the control. This study therefore corroborates the study of Amini et al () who reported on the relationship between fluoride concentrations in ground water and the incidence of high blood pressure in the exposed population. Nitric oxide produced from the vascular endothelium helps to maintain a continuous vasodilator tone that is essential for the regulation of blood flow, blood pressure, platelet aggregation and vasodilation (Hermann et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Amini et al . reported an ecological study on the relationship between fluoride concentrations in ground water and blood pressure in an Iranian population. Several human studies have also examined the relationship between excessive fluoride intake from drinking water and hypertension (HT).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of acute fluoride toxicity are well documented in the literature (Mannina et al 2013). Some fluoride-related diseases include genetic mutations, birth defects, infants' height and weight disorders (Aghaei et al 2015), increased allergic reactions, allergic diseases, damage to bones, abnormal skeletal effects, Fluorosis (Azami-Aghdash et al 2013), blood pressure (Amini et al 2011), fertility effects, effects on kidney and liver (Xiong et al 2007), neurological effects, impaired intelligence of children (Seraj et al 2012;Karimzade et al 2014;Anna and Guifan 2012;Nagarajappa and Pujara 2013), hyperactivity (Ashley and Till 2015), thyroid hormone effects (Sachdeva et al 2015;Momeni and Dehghani 2011;Swati and Shashi 2013;Coperchini and Pignatti 2015;Vandana et al 2015;Susheela 2005;Wolka et al 2014), carotid atherosclerosis (Liu et al 2014), cancerous effects, and Alzheimer's disease; in spite of these, more studies are needed in this area (David and Ozsvath 2009;Mannina et al 2013). Linear regression analyses by Dobaradaran et al (2008a, b) showed weak increases of the number of decayed permanent teeth and the number of decayed deciduous teeth scores with increasing water F levels (Dobaradaran et al 2008a, b).…”
Section: Introductionmentioning
confidence: 99%